2015
DOI: 10.5604/20831862.1173644
|View full text |Cite
|
Sign up to set email alerts
|

Sprint interval training (SIT) is an effective method to maintain cardiorespiratory fitness (CRF) and glucose homeostasis in Scottish adolescents

Abstract: The present study examined the physiological impact of a school based sprint interval training (SIT) intervention in replacement of standard physical education (SPE) class on cardio-respiratory fitness (CRF) and glucose homeostasis during the semester following summer vacation. Participants (n=49) were randomly allocated to either intervention (SIT; n=26, aged 16.9 ± 0.3 yrs) or control group who underwent standard physical education (SPE; n=23, aged 16.8 ± 0.6 yrs). CRF (VO2max) and glucose homeostasis were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 40 publications
2
52
3
2
Order By: Relevance
“…Our findings from the current study reported a significant improvement in CRF following 4 weeks of school-based SIT (Table 3; Figure 2). These findings are in contrast with previous work from our group that reported a maintenance of CRF following a 7-week school-based SIT in 15-17 year-old adolescents (34). The difference in findings between the 7-week SIT study and the current 4-week SIT study may be a consequence of the higher average intensity (%HRmax) of SIT observed in this current study compared with our previous work (92% of HRmax Vs 87% of HRmax, respectively).…”
Section: Cardiorespiratory Fitnesscontrasting
confidence: 99%
See 4 more Smart Citations
“…Our findings from the current study reported a significant improvement in CRF following 4 weeks of school-based SIT (Table 3; Figure 2). These findings are in contrast with previous work from our group that reported a maintenance of CRF following a 7-week school-based SIT in 15-17 year-old adolescents (34). The difference in findings between the 7-week SIT study and the current 4-week SIT study may be a consequence of the higher average intensity (%HRmax) of SIT observed in this current study compared with our previous work (92% of HRmax Vs 87% of HRmax, respectively).…”
Section: Cardiorespiratory Fitnesscontrasting
confidence: 99%
“…Our previous work found that 7 weeks of school-based running SIT implemented in the first term of school following a summer vacation period maintained CRF, insulin and glucose homeostasis compared with age matched controls receiving standard PE classes in healthy adolescents (34). We also reported that the SIT cohort subjectively self-selected greater levels of PA during this study, compared 5 with control participants and that the control group experienced a small decrease in CRF during the school term.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations